Implementation of metadata for OmniPaper RDF prototype - Yaginuma, T. (2004)
Information Society Technologies (IST) funded OmniPaper project investigates efficient ways for access to distributed and heterogeneous digital news archives using state-of-the-art technologies such as RDF, XTM and SOAP. An approach taken is to create small prototypes based on each of them. This paper presents the first stage of the prototype development, particularly of RDF approach, including analysis on existing news text format standards and metadata vocabularies, definition of metadata elements for OmniPaper, implementation of application profile and RDF schema and development of the RDF prototype in a web-based RDF specific application. The elaborated analysis shows that Dublin Core Metadata Element Set has to be a principal vocabulary to implement the OmniPaper application profile as it provides greater interoperability. The RDF prototype provides RDF “metadatabase” with searchable interface for simple and advance search on the defined metadata elements.